Assessing undergraduate learning in psychology : strategies for measuring and improving student performance - Nolan, Susan A.; Hakala, Chris; Landrum, R. Eric (American Psychological Association, 2021)
"This book describes best practices for developing assessments that undergraduate psychology faculty and administrators can use when designing courses and curricula around student learning goals, including those identified in APA's Guidelines for the Undergraduate Psychology Major. Veteran educators draw on their expertise to provide guidance for addressing three common types of assessment pressures-individual, institutional, and international-to help other educators meet the needs of multiple stakeholders while ensuring that students have the skills to compete in the global economy"--